Faktor Yang Berpengaruh Terhadap Kelelahan Kerja Pada Pekerja Bongkar Muat Barang - Giranza, Virgian; Utami, Tri Niswati; Nanda, Meutia; Hasibuan, Rapotan; Peralihan, Hotmatua (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2025)
Fatigue is a protective mechanism of the body to prevent injury, allowing recovery to occur during periods of rest. Truck freight activities are still dominated by manual labor, in which this working pattern is highly physically demanding and accelerates the fatigue experienced by workers. This study aims to determine the factors that influence work fatigue among loading and unloading workers in truck freight on Sunggal Street, Tanjung Rejo Sub-district. This type of research is quantitative with a cross-sectional design. The sampling technique used in this study was total sampling, involving 60 loading and unloading workers in truck freight on Sunggal Street, Tanjung Rejo Sub-district. Data collection was conducted using the Rapid Entire Body Assessment questionnaire, the NIOSH Lifting Equation, and the Swedish Occupational Fatigue Inventory. Data analysis used multiple linear regression. The results showed significance values for the variables of age (0.594), working time (0.046), length of service (0.286), working posture (0.441), and lifting index (0.000). There was a significant partial effect of the variables working time, and lifting index on work fatigue. There was no significant effect of the variables age, length of service, and working posture on work fatigue. There was a simultaneous effect of the independent variables on the work fatigue variable with a p-value of (0.014). Workers need to pay attention to load weight, vertical load location, vertical distance, lifting frequency, coupling/handle, and lifting aids should be provided to reduce the risk of harm to workers.